TRADE BUSINESS DEVELOPMENT STRATEGY IN KPRI PRAJA WIBAWA COOPERATION, LHOKSEUMAWE CITY - Afriliana, Lusi; Safrina, Safrina; Anita, Leli; Yanti, Riska; Nur Ilham, Rico (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Cooperatives are a form of legal entity that exists in Indonesia. The purpose of this research is to develop a cooperative strategy for Lhokseumawe Regency and the Satpol PP and WH offices of Lhokseumawe City in efforts to develop small businesses in Lhokseumawe Regency today. This search uses a qualitative descriptive approach. This type of research is field research. The results of this study are analyzed using the inference method which begins with general data and ends with conclusions. Based on the results of the research, it can be concluded that the previous trading business development strategy in Lhokseumawe Regency was through third parties, such as banks, investors, and for the development of this cooperative, this cooperative was carried out in a friendly manner with related agencies.